Antimony and arsenic partitioning during Fe2+-induced transformation of jarosite under acidic conditions. (March 2018) - Karimian, Niloofar; Johnston, Scott G.; Burton, Edward D.
Abstract: Jarosite [KFe3 (SO4 )2 (OH)6 ] is considered a potent scavenger for arsenic (As) and antimony (Sb) under oxidizing conditions. Fluctuations in water levels in re-flooded acid sulfate soils (ASS) can lead to high Fe 2+ (aq) concentrations (∼10–20 mM) in the soil solution under acidic to circumneutral pH conditions. This may create favorable conditions for the Fe 2+ -induced transformation of jarosite. In this study, synthetic arsenate [As(V)]/antimonate [Sb(V)]-bearing jarosite was subjected to Fe 2+ (aq) (20 mM) at pH 4.0 and 5.5 for 24 h to simulate the pH and Fe 2+ (aq) conditions of re-flooded freshwater ASS/acid mine drainage (AMD)-affected environments at early and mid-stages of remediation, respectively. The addition of Fe 2+ at pH 5.5 resulted in the formation of a metastable green rust sulfate (GR- SO4 ) phase within ∼60 min, which was replaced by goethite within 24 h. In contrast, at pH 4.0, jarosite underwent no significant mineralogical transformation. Although the addition of Fe 2+ (aq) induced the dissolution/transformation of jarosite at pH 5.5 and increased the mobility of Sb during the initial stages of the experiment (Sb(aq) = ∼0.05 μmol L −1 ), formation of metastable green rust (GR-SO4 ) and subsequent transformation to goethite effectively sequestered dissolved Sb. Aqueous concentrations of As remained negligible in both pH treatments, with As being mostly repartitioned to the labile (∼10%) and poorly crystalline Fe(III)-associated phases (∼10–30%). The results imply that, under moderately acidic conditions (i.e. pH 5.5), reaction of Fe 2+ (aq) with jarosite can drive the dissolution of jarosite and increase Sb mobility prior to the formation of GR-SO4 and goethite. In addition, repartitioning of As to the labile fractions at pH 5.5 may enhance the risk of its mobilisation during future mineral transformation processes in Fe 2+ -rich systems. Graphical abstract: Highlights: At pH 4.0, the addition of Fe 2+ (aq) resulted in no significant transformation in jarosite. At pH 5.5, 60 min was sufficient for partial transformation of jarosite to green rust. Formation of green rust and goethite under pH 5.5, sequestered dissolved antimony. Arsenic was mostly repartitioned to the surface of green rust and goethite.